Radiolysis of astrophysical ices by heavy ion irradiation: destruction cross section measurement - Barros, A.L.F. de; Boduch, P.; Domaracka, A.; Rothard, H.; Silveira, E.F. da (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2012)
Many solar system objects, such as planets and their satellites, dust grains in rings, and comets, are known to either be made of ices or to have icy surfaces. These ices are exposed to ionizing radiation including keV, MeVand GeV ions from solar wind or cosmic rays. Moreover, icy dust grains are present in interstellar space and in particular in dense molecular clouds. Radiation effects include radiolysis (the destruction of molecules leadingto formation of radicals), the formation of new molecules following radiolysis, the desorption or sputtering of atoms or molecules from the surface, compaction of porous ices, and phase changes. This review discusses the application of infrared spectroscopy FTIR to study the evolution of the chemical composition of ices containing the most abundant molecular species found in the solar system and interstellar medium, such as H2O, CO, CO2and hydrocarbons. We focus on the evolution of chemical composition with ion fluence in order to deduce thecorresponding destruction and formation cross sections. Although initial approach focused on product identification, it became increasingly necessary to work toward a comprehensive understanding of ice chemistry. The abundances of these molecules in different phases of ice mantles provide important clues to the chemical processes in dense interstellar clouds, and therefore it is of importance to accurately measure the quantities such as dissociation and formation cross sections of the infrared features of these molecules. We also are able to obtain the scaling of these cross sections with deposited energy.